Gambaran Pengetahuan Manfaat Pemakaian Gigi Tiruan pada Siswa-siswi SMA Ananda Bekasi - Jennifer Ferdiana; Andy Wirahadikusumah (Fakultas Kedokteran Gigi Universitas Trisakti, 2022)
Background: Tooth loss is one of the dental and oral health problems that can affect the stomatognathic and emotional systems of adolescents. These changes in students especially aged 16-18 years old, can generate dental and oral health problems, one of which is tooth loss and can be solved with the use of dentures. Riskesdas Province of West Java (2018) showed a gap between the proportion of permanent teeth loss in adolescent (9,04%) with the use of denture (0,34%) and implant denture (0,15%) in adolescents of age group 15-24 years old. Objective: Determine knowledge of students aged 16-18 years old about the benefits of using dentures at Ananda Bekasi School. Method: Descriptive observational study with a cross-sectional research design. The study was conducted by distributing questionnaires related to knowledge in students aged 16-18 years old at Ananda Bekasi School. Results: fifty respondents participated in this study had a good knowledge about the benefit of denture use, with an average score of 71,96%. Middle adolescents had lower knowledge than late adolescents. Both genders demonstrated good scores. Conclusion: The majority of adolescent aged 16-18 years old in Ananda Bekasi School possessed a good knowledge about denture use.